Les marques sur les récipients en verre découverts en Gaule : indices de production et de relations commerciales (milieu du ier s.-ve s. apr. J.-C.) - Danièle Foy (Gallia)
Several old and new works have been done on marked Roman glass. Here, we try to gather the most significant documentation about bottles and flasks, to explain Gallic productions and imports. These containers, used between the mid-1st c. AD and the 5th c. didn’t attract the nonspecialists’ attention. However, like other bigger packages, these jars, in various shapes and with marks of different sizes, enable us to locate production areas and detect the short and long-distance trade flows. The meaning of these marks can yield several different interpretations, but it seems they mainly refer to the content, or to those who benefit from it.